The Practical Analysis of Innovation and HRM Practices - Gao, Jie (2016)
Innovation contributes to the achievement and maintenance of organizational performance and has been considered as a key factor to ensure success in the competitive environment. Plentiful empirical studies suggest a positive relationship between HRM practice and Innovation, but the question of how HRM practices affect innovation performance, especially in practice, remains to be discussed. Therefore, this dissertation aims at exploring how to motivate employees to innovate through HRM practices in the context of emerging market. Considering the nature of research, case study method in qualitative research approach was employed, along with a total of 20 in-depth semi-structured interviews. Combining the case analysis with the evaluation of HRM practice and motivation theories, the findings have shown that effective performance appraisal, attractive reward package, specific job design contributes greatly to employee’s innovation performance. Moreover, this research discovered that the intrinsic motivators, learning corporate culture and teamwork are conducive to promote creativity. This dissertation also suggested several practical implications from the results of this study. The recommendations to motivate R&D employees could be applied to other knowledge workers. In addition, the contribution and limitation of this research and suggestions for further studies are also been provided.